70. Laser-evoked potentials (LEPs) in chronic pain conditions during hypnotic analgesia. Issue 12 (December 2017) - Matinella, A.; Brugnoli, M.P.; Pasin, E.; Segatti, A.; Concon, E.; Squintani, G.
Abstract : Hypnotic analgesia represents one of the most effective nonpharmacological methods for pain control. Hypnosis and distraction from pain might share similar mechanisms, implying that brain responses to painful stimulation should be similarly reduced in both situations. Literature data are conflicting, showing increase, reduction or no change in Event-Related Brain Potentials amplitudes during hypnosis compared to control conditions. Here we investigate effects of hypnosis and distraction during laser-evoked potentials (LEPs) in patients with chronic painful diseases. 9 patients with chronic pain were studied with LEPs on the dominant hand during resting state, medium and deep hypnosis (techniques for analgesia), and focused attention on article reading. Pain induced by LEPs was assessed with Numerical Rating Scale (NRS) and we analyzed N2/P2 complex amplitude change during the three conditions. Patients under hypnosis showed significant N2/P2 amplitudes decrease compared to resting state and distraction. Hypnosis is a physiological modified state of consciousness that may differ either from mental relaxation or distraction from pain. N2/P2 amplitude reduction may depend on different brain networks activation, in particular frontolimbic pathways, which could modify noxious stimuli input processing during hypnotic analgesia. Our results indicate that different brain mechanisms might act in hypnosis and distraction during pain processing.